Impact of electron-scale turbulence and multi-scale interactions in the JET tokamak. (28th September 2018) - Bonanomi, N.; Mantica, P.; Citrin, J.; Goerler, T.; Teaca, B.
Abstract: Experimental observations in JET tokamak plasmas and gyrokinetic simulations point to an important role, for electron heat transport, of electron-scale instabilities and of their interaction with ion-scale instabilities. Since these effects are maximized for strong electron heating and ion-scale modes close to marginal stability, these findings are of high relevance for ITER plasmas, featuring both conditions. Gyrokinetic and quasi-linear transport models accounting for multi-scale effects are assessed against JET experimental results.